Radiology Illustrated: Chest Radiology - Lee, Kyung Soo; Han, Joungho; Chung, Man Pyo; Jeong, Yeon Joo (Radiology Illustrated, 2014)
The purpose of this atlas is to illustrate how to achieve reliable diagnoses when confronted by the different abnormalities, or "disease patterns", that may be visualized on CT scans of the chest. The task of pattern recognition has been greatly facilitated by the advent of multidetector CT (MDCT), and the focus of the book is very much on the role of state-of-the-art MDCT. A wide range of disease patterns and distributions are covered, with emphasis on the typical imaging characteristics of the various focal and diffuse lung diseases. In addition, clinical information relevant to differential diagnosis is provided and the underlying gross and microscopic pathology is depicted, permitting CT-pathology correlation. The entire information relevant to each disease pattern is also tabulated for ease of reference. This book will be an invaluable handy tool that will enable the reader to quickly and easily reach a diagnosis appropriate to the pattern of lung abnormality identified on CT scans.